2017
DOI: 10.5606/archrheumatol.2017.6222
|View full text |Cite
|
Sign up to set email alerts
|

What Impairs Balance in Ankylosing Spondylitis? Posture or Disease Activity?

Abstract: Objectives:This study aims to compare ankylosing spondylitis (AS) patients with healthy subjects in terms of posture and balance, and to identify the factors correlated with balance in AS. Patients and methods: Thirty patients (17 males, 13 females; mean age 41.7±7.7 years; range 31 to 57 years) with AS and 33 healthy subjects (18 males, 15 females; mean age 41.3±7.0 years; range 26 to 56 years) were included in the study. Participants were assessed in terms of posture and balance. Posture was assessed using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…Likewise, studies evaluating balance through various methods in the presence of AS showed a higher extent of balance loss in AS when compared to healthy subjects. [29][30][31] Similar to prior clinical studies, the findings of the present study showed that AS patients experienced a greater loss of balance than healthy subjects. Poor balance is a significant risk factor for falls.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, studies evaluating balance through various methods in the presence of AS showed a higher extent of balance loss in AS when compared to healthy subjects. [29][30][31] Similar to prior clinical studies, the findings of the present study showed that AS patients experienced a greater loss of balance than healthy subjects. Poor balance is a significant risk factor for falls.…”
Section: Discussionsupporting
confidence: 89%
“…However, when the literature is examined, it has been seen that studies evaluating balance in individuals with AS are limited and there is no specific tool to examine balance. In previous studies, Berg Balance Scale, force plate, Biodex Stability System, and magnometry were used to evaluate dynamic or static balance in AS patients [14][15][16]31]. The use of different measurement tools makes it difficult to interpret the relationship between AS and balance.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, mediolateral sway was similar in AS patients and controls. Gündüz et al[ 21 ] demonstrated impairment of both static and dynamic balance in AS patients, with static balance impaired in the eyes-closed condition. Vergara et al[ 2 ] reported a significantly greater CoP displacement in the AS group when tested on a ‘force platform’ with the eyes closed.…”
Section: Discussionmentioning
confidence: 99%